2015
DOI: 10.1049/htl.2015.0019
|View full text |Cite
|
Sign up to set email alerts
|

Review: Are we stumbling in our quest to find the best predictor? Over‐optimism in sensor‐based models for predicting falls in older adults

Abstract: The field of fall risk testing using wearable sensors is bustling with activity. In this Letter, the authors review publications which incorporated features extracted from sensor signals into statistical models intended to estimate fall risk or predict falls in older people. A review of these studies raises concerns that this body of literature is presenting over-optimistic results in light of small sample sizes, questionable modelling decisions and problematic validation methodologies (e.g. inherent problems … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
68
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(72 citation statements)
references
References 85 publications
2
68
0
2
Order By: Relevance
“…accelerometers and gyroscopes) attached to the subject's body during specific assessment tasks (e.g. walking, quiet standing, sit-to-stand transitions) [9]- [11]. In those studies, machine learning methods were used to automatically identify fallers (F) and non-fallers (NF).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…accelerometers and gyroscopes) attached to the subject's body during specific assessment tasks (e.g. walking, quiet standing, sit-to-stand transitions) [9]- [11]. In those studies, machine learning methods were used to automatically identify fallers (F) and non-fallers (NF).…”
Section: Introductionmentioning
confidence: 99%
“…Howcroft et al [9] and Shany et al [11] have presented insightful accounts of features, classification models and validation strategies related to sensor-based fall-risk testing (SFRT). In their investigations, these authors found large heterogeneity in terms of sensor placement, tasks assessed, and sensor-based features.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in geriatric fall prediction [18], pooling activity and falls data collected by wearable sensors across multiple studies, and making them open access, may enable the development of better prediction models. In fact, 'intellectual crowdsourcing' is the basis of Kaggle [19], an online platform where researchers and companies, both within and outside of healthcare, post datasets to crowdsource statistical and data mining labor via competitions to find the best predictive models.…”
Section: Benefits Of Data Sharingmentioning
confidence: 99%
“…In the analysis of sensor data for ambulation and falls we learnt that many research groups worldwide fell into analysis and methodological traps that limit the generalizability and usefulness of some of the analyses and models reported in the literature. Some of the associated issues and lessons learnt are summarized in [119] and include overly-optimistic results in light of small sample sizes, questionable modelling decisions, and problematic validation methodologies. With the enormous increase in availability of rich sensor data and many possible analytical approaches, researchers are provided with the intellectual and creative freedom to explore datasets without constraints.…”
Section: Lessons Learned?mentioning
confidence: 99%